(untitled) (Ad Aeternum, 2026)
The author’s aim is to provoke deeper research to two influential movements, Religious Nationalism and Populism, in such a way that will produce not only insight in what was vaguely known but the deeper details of how these movements can come up with such a compromise, results and the consequences of this new alliance. We’ve seen a surge within the political arena of leaders and movements, over the past decade, that heavily emphasize religious identity, morality, and rhetoric. This has been a notable shift in many countries around the world including in Europe. The blending of religious nationalism and populism presents a major hurdle for liberal democracy in our world today. In many regions of the world, religious nationalism—in which the identity of a country is strongly associated with the main religion—has become more prevalent in recent years. On the other hand, the Populist discourse that sets “the people” against “the elite” or other outgroups is frequently used in conjunction with this. The appeal to traditional values and beliefs, presenting themselves as protectors of a threatened religious and cultural identity against secular, progressive, or globalist forces has been an effective tool used by both camps and the platform for their understanding. Although they are typically recognized as separate political phenomena, each one has its own unique intricacies and outcomes. To understand religious nationalism and populism, one must carefully examine the theoretical underpinnings, historical contexts, and social dynamics of each movement. The blending of the two is complex but the results are being seen in many countries in the world today bringing a new paradigm to the politic scene impacting all spheres of global society. In this paper there is a search to provide a vision of the characteristics of the two spheres and the product resulting from the exercise of their blending. For this end the research looked for credible documentation, political papers, books and research done by credible and proven scientific entities. The current developments and events in the political speres including the recent elections in many countries in the world are bringing to surface a new and unexpected twist giving notorious space to not only to the religious nationalism but bringing up evidence of an astronomic growing of the religious populism in places of power. A number of factors have contributed to the development of religious populism, including social media’s popularity, cultural backlash, economic distress, and the efficiency of certain demagogic political tactics. The notorious recent examples of Argentina, Brazil, U.S.A., France, Italy and most lately Portugal, determine the need for this investigation in a way to understand not only the basis of it but its progress. Therefore, future research certainly will be done to understand the evolving dynamics within societies, where faith-based identity and populist narratives intersect to shape political outcomes due to the fact that This is because it presents new concerns and challenges for the future of democracy and government.